Measurement method for deformation and contact force of the fuel assembly for China fast reactor under thermal gradient. (15th June 2020) - Wang, Kaiqiang; Chen, Hong-En; Shi, Pengpeng; Li, Lijuan; Xie, Shejuan; Chen, Zhenmao; Hei, Baoping; Gao, Fuhai; Yang, Hongyi; Wu, Yingwei; Su, Guanghui
Abstract: Deformation and contact force of the fuel assembly due to thermal gradient are of great concerns to the integrity design and safe operation of the core in the China Fast Reactor (CFR). Up to now, only the 2D deflection measurement of the sub-assemblies has been investigated, and almost no attention is paid to the contact force measurement between the sub-assemblies with a small clearance. In this paper, the measurement method and system are developed for measuring the deformation and contact force of the fuel assembly under thermal gradient with the test fuel assembly simplified based on the stiffness equivalent strategy. In addition, the 3D deformation and contact force are measured through the non-contact industrial photogrammetry system and the thin film pressure sensor or strain gauge, respectively. Free thermal bowing test for a single assembly is performed at first for verifying the reliability of the 3D deformation measurement by comparing with the results of finite element (FE) simulation. Afterwards, the 3D deformation and the contact force are measured for the single assembly restrained thermal bowing test. The accuracy of the proposed contact force measurement is investigated through comparison with the method of spoke-type force sensors. The developed measurement method and system can provide experimental basis for safety design of the CFR due to its potential for comprehensive deformation and contact force measurements.